2008
DOI: 10.1021/np800248s
|View full text |Cite
|
Sign up to set email alerts
|

Furan Oligomers and β-Carbolines from Terrestrial Streptomycetes

Abstract: 2,5-Bis(hydroxymethyl)furan monoacetate (3) and 2,5-bis(hydroxymethyl)furan diacetate (4) were obtained as new natural products from an ethyl acetate extract of the terrestrial Streptomyces sp. isolate GW11/1695. Another Streptomyces isolate, GW21/1313, delivered a dimer (6) and a trimer (7) of (hydroxymethyl)furfural. The latter strain also produced 4-hydroxy-2-(5-(hydroxymethyl)furan-2-ylmethylene)-5-methylfuran-3-one (5), perlolyrin (8), and two new beta-carboline derivatives, 9 and 10. 2,5-Bis(hydroxymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…These findings were further confirmed by comparing the physical and spectral data with the values described in the literature (Fotso et al . ). The BHMF‐OAc is a derivative of a broader class of furans including five‐membered heterocyclic, oxygen‐containing, unsaturated ring compound.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings were further confirmed by comparing the physical and spectral data with the values described in the literature (Fotso et al . ). The BHMF‐OAc is a derivative of a broader class of furans including five‐membered heterocyclic, oxygen‐containing, unsaturated ring compound.…”
Section: Resultsmentioning
confidence: 97%
“…Previous research of Fotso et al . () reported that the BHMF‐OAc was isolated from an EtOAc extract of the terrestrial Streptomyces sp. isolate GW11/1695, however, they did not evaluate the antimicrobial activity of the compound.…”
Section: Resultsmentioning
confidence: 99%
“…They are widely distributed in various plants, whereas only a few reports are available on the ␤-carboline compounds from bacterial origins (11). With respect to the biosynthetic pathway of ␤-carboline alkaloids, strictosidine synthase (STR1) of Rauvolfia serpentina (STR1; accession no.…”
Section: Discussionmentioning
confidence: 99%
“…The amplified fragment was treated with DpnI to remove a template DNA and digested with Bal31 for 30 s at 30°C. The biosynthetic gene cluster for kitasetaline in pKU503facP2-L12 was replaced by a linear molecule of pRED::upstream:: downstream using the homologous regions using the RED recombination system (E. coli DH10B and pKD119 were used [21]) to generate pRED::ksl (kitasetaline) cluster (11,141 bp, corresponding to nt 8040461 to 8051601 of K. setae). A XbaI/HindIII fragment, including an 11.1-kb ksl cluster, recovered from pRED::ksl, was inserted into the XbaI/HindIII sites of pKU492Aaac(3)IV, resulting in the pKU492Aaac(3)IV::ksl cluster, named pLT437.…”
Section: Methodsmentioning
confidence: 99%
“…The β-carboline alkaloids are widely distributed in various plants, whereas there are only a few reports of the β-carboline compound in actinomycetes (14) and filamentous fungi (15). This is the first report on the isolation of β-carboline alkaloid from Kitasatospora spp.…”
mentioning
confidence: 87%